Association of postoperative infection and oncological outcome after breast cancer surgery. Issue 4 (8th July 2021) - Adwall, L; Pantiora, E; Hultin, H; Norlén, O
Abstract: Background: Surgical-site infection (SSI) is a well known complication after breast cancer surgery and has been reported to be associated with cancer recurrence. The aim of this study was to investigate the association between SSI and breast cancer recurrence, adjusting for several known confounders. The secondary aim was to assess a possible association between any postoperative infection and breast cancer recurrence. Method: This retrospective cohort study included all patients who underwent breast cancer surgery from January 2009 to December 2010 in the Uppsala region of Sweden. Data collected included patient, treatment and tumour characteristics, infection rates and outcome. Association between postoperative infection and oncological outcome was examined using Kaplan–Meier curves and Cox regression analysis. Results: Some 492 patients (439 with invasive breast cancer) with a median follow-up of 8.4 years were included. Mean(s.d.) age was 62(13) years. Sixty-two (14.1 per cent) of those with invasive breast cancer had an SSI and 43 (9.8 per cent) had another postoperative infection. Some 26 patients had local recurrence; 55 had systemic recurrence. Systemic recurrence was significantly increased after SSI with simple analysis (log rank test, P = 0.035) but this was not observed on adjusted analysis. However, tumour size and lymph node status remained significant predictors for breast cancer recurrence on multiple regression. Other postoperative infections were not associated with recurrence. Conclusion: Neither SSI nor other postoperative infections were associated with worse oncological outcome in this study. Rather, other factors that relate to both SSI and recurrence may be responsible for the association seen in previous studies. Abstract : Surgical site infection (SSI) is a well-known complication after breast cancer surgery and some previous studies suggest that SSI may increase the risk for breast cancer recurrence. In this population-based, retrospective cohort study we wanted to examine this possible association and also investigate if other postoperative infections were associated with breast cancer recurrence. The present study does, however, not support the hypothesis that postoperative SSI increases the rate of breast cancer recurrence.